The particularities of the polyphonic thinking development of students receiving higher education in arts - Дорош, Т. Л.; Недомолкіна, С. Л. (Scientific notes of the pedagogical department, 2019)
The article considers persistent problems of polyphonic thinking development of students receiving higher education in arts. Special attention is paid to the choice of musical repertoire with polyphonic structure which favorizes students’ more conscious and interested perception of musical culture in different countries of the world, their better understanding of complex polyphonic compositions during their following education. Is it proposed for students with uncompleted music education to take polyphonic pieces with easy structure, with prevailing melody but with melodic and dynamically varied second voice, to learn during the classes of special music instrument. For students with full music education we propose to take Bach’s polyphonic pieces where the harmony between all the voices is required. Special attention is paid to it as every voice has its own breathing, pace, tone, character, and emotional expression. The article contains examples of a practical music lesson with 6-grade schoolchildren for which the trainee student chose polyphonic form. Using her polyphonic thinking she was able to conduct an integrated arts lesson dedicated to chamber instrumental music, nocturn in particular. The future arts teacher appealed to literature (O. Pushkin’s «Poltava» poem, M. Hohol’s «Evenings on a Farm Near Dykanka» stories), music (F. Chopin’s and A. Babadzhanian’s pieces), painting (A. Kuindzhi’s «Ukrainian night» and «Moonlit night upon the Dnipro»), singing (Vira Drobotenko’s «Lullaby for future»). Such a variety of material enabled the participants to consider cultural phenomena taking place in the world of today in their integrity. Another instance is given: the example of cultural and artistic event «Dance rhythms from around the world» where the artistic image of the music pieces was presented through instrumental music performances (dance rhythms of galop, tango, boogie-woogie, waltz etc.), visual arts (slides, personal photography, images, videos) and 4-lines poems. It is proved that such a multi-dimensionality favorizes the polyphonic thinking development which is an essential marker in educational process for future professionals’ orientation in sociocultural environment.